Sistem Peringatan Dini Untuk Pengendalian Pembatasan Jarak Fisik Dengan Metode RSSI Menggunakan Modul Wemos D1 Mini - Noni Mastiana; Ardian Ulvan; Melvi Ulvan (Universitas Syiah Kuala, 2021)
Covid-19 was first reported in Indonesia in March 2020. A month later the confirmed cases had reached 1528 cases and the death toll was 136 cases. Distance restrictions, also known as physical and social distance, are one of the government's efforts to reduce the rate of increase in the number of positive Covid-19 patients. However, this policy is still not fully effective, due to the low level of community compliance. When personal awareness has not been awakened, the use of technology in the context of early warning to maintain distance is an effective solution. This article discusses the use of received signal strength indicator (RSSI) from the Wemos D1 Mini module as a model of an early warning system device to anticipate unsafe distances when someone is in a crowd. The use of RSSI in this study shows that the device made works well, where the alarm is active when the distance between devices is 1 meter. The system performance was analyzed by calculating and measuring the average RSSI error value of -34.46 dBm and the average distance error of 0.26 meters. Overall, the early warning system using this method can be used properly to estimate physical distance restrictions during a pandemic.